Association between cord blood IgE levels in newborns and family history of atopic diseases - Andhika T. Hutapea; Budi Setiabudiawan; Myrna Soepriadi; Diet Sadiah Rustama (Indonesian Pediatric Society Publishing House, 2016)
Background Cord blood-IgE (CB-IgE) levels have been used widely as a specific marker of atopic diseases. In some previous studies, CB-IgE levels in subjects with and without a family history of atopic diseases have been controversial. Objective To determine the CB-IgE level in newborns and to iden- tify the association between CB-IgE and family history of atopic diseases. Methods A cross-sectional study was done to compare the CB-IgE levels in neonates with or without a family history of atopic diseases in mother, father, or siblings. Subjects of this study were 124 new- borns who consecutively born in Puskesmas Kiaracondong, Bandung, during the period of March 2001 to July 2002. Subjects were divided into 2 groups based on history of atopic diseases. Measurements of CB-IgE levels were done by sandwich ELISA methods. Data were analyzed by c 2 statistics, t test, ANOVA, and Dunkan's test. Results The mean CB-IgE levels in the group with and without a family history of atopic diseases were 3.2±2.5 IU/ml and 0.5±0.5 IU/ml (P<0.001), respectively. The mean CB-IgE levels in male and female infants with a family history of atopic diseases were 3.3±2.7 IU/ml and 3.03±2.2 IU/ml (P>0.05), respectively. Based on the cut-off point (1.3 IU/ml), CB-IgE levels had significant posi- tive association with a family history of atopic diseases (OR 156, 95%CI 29.61;1104.24). CB-IgE levels in neonates with 1, 2, and 3 atopic family members were 1.67±0.78 IU/ml, 3.76±2.11 IU/ml, and 6.6±2.7 IU/ml, respectively (F=32.603; P<0.001). Conclusion Most newborns with a family history of atopic dis- eases showed high levels of CB-IgE, but there were no correlation with gender. The probability of having atopic diseases increase in concord with the number of family with atopic diseases